Rational Use of Antibiotics at a Pharmacy in Kotamobagu - Astuti, Windi; Kuna, Moh Rasyid (Borobudur Pharmacy Review, 2025)
Infectious diseases remain an important public health problem, especially in developing countries. One of the mainstay therapies for overcoming this problem is the use of antibiotics. Irrational prescribing and use of antibiotics have a significant impact on human health, one of which is the development of microbial resistance to antibiotics. The purpose of this study was to obtain information on the proportion of antibiotics prescribed among all drugs dispensed at a pharmacy in Kotamobagu City during the January”“March 2024 period. This study used a descriptive research design with retrospective data collection based on prescription records. The collected data were analyzed using the 90% Drug Utilization (DU) segment method. The results showed that antibiotics accounted for 62.85% of all prescribed drugs. The antibiotic groups included in the 90% DU segment were cephalosporins, chloramphenicol, and quinolones. The findings indicate a shift in antibiotic use, with cephalosporins being the most widely used group. This suggests possible resistance to penicillin-group antibiotics in the region. Therefore, rational use of antibiotics by prescribers and pharmacists is essential to reduce the development and spread of antibiotic resistance in the region.